COMPLEX RECONSTRUCTION OF THE CONTINUOUS CASTING MACHINES OF BELARUSIAN STEEL WORKS - A. A. Sotnikov; A. V. Demin; S. V. Terletsky (Литьë и металлургия)
Set of activities performed by the machine for continuous casting mill № 3 has enhanced its productivity and also master a new product - continuous casting round billet for seamless drawn pipes in tube-rolling shop